Pengaruh Kualitas Pelayanan dan Kecepatan Respons Terhadap Kepuasan Pelanggan di Restoran Marugame Udon - Anindya Najmina Nareswari; Adhila Suryaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the influence of service quality and response speed on customer satisfaction at Marugame Udon restaurant. Through a literature review, this study examines various theories and previous research related to service quality, response speed, and customer satisfaction. The findings indicate that both service quality, which includes tangibles, reliability, responsiveness, assurance, and empathy, as well as response speed in serving customers, have a significant impact on customer satisfaction. Good service quality and high response speed can enhance customers' perception of the value offered by the restaurant and encourage customer loyalty. The implication of this research is the importance for the restaurant to continuously strive to improve service quality and response speed in order to maintain and enhance customer satisfaction